Research priorities for autosomal dominant polycystic kidney disease: a UK priority setting partnership. Issue 6 (15th June 2022) - Harris, Tess; Bridges, Hannah R; Brown, Wendy D; O'Brien, Natasha L; Daly, Ann C; Jindal, Bharat K; Mundy, Gillian S; Ong, Albert; Power, Albert J; Sandford, Richard N; Sayer, John; Simms, Roslyn J; et al.
Abstract : Objectives: Autosomal dominant polycystic kidney disease (ADPKD) is the most common inherited kidney condition, accounting for 7%–10% of patients with kidney failure. Fundamental basic science and clinical research on ADPKD is underway worldwide but no one has yet considered which areas should be prioritised to maximise returns from limited future funding. The Polycystic Kidney Disease Charity began a priority setting partnership with the James Lind Alliance (JLA) in the UK in 2019–2020 to identify areas of uncertainty in the ADPKD care pathway and allow patients, carers and healthcare professionals to rank the 10 most important questions for research. Design: The scope covered ADPKD diagnosis and management, identifying new treatments to prevent/slow disease progression and practical, integrated patient support (https://pkdcharity.org.uk/research/for-researchers/adpkd-research-priorities ). We used adapted JLA methodology. Initially, an independent information specialist collated uncertainties in ADPKD care from recent consensus conference proceedings and additional literature. These were refined into indicative questions with Steering Group oversight. Finally, the 10 most important questions were established via a survey and online consensus workshop. Setting: UK. Participants: 747 survey respondents (76% patients, 13% carers, 11% healthcare professionals); 23 workshop attendees. Results: 117 uncertainties in ADPKD care were identified and refined into 35 indicative questions. A shortlist of 17 questions was established through the survey. Workshop participants reached agreement on the top 10 ranking. The top three questions prioritised by patients, carers and healthcare professionals centred around slowing disease progression, identifying persons for early treatment and organising care to improve outcomes. Conclusions: Our shortlist reflects the varied physical, psychological and practical challenges of living with and treating ADPKD, and perceived gaps in knowledge that impair optimal care. We propose that future ADPKD research funding takes these priorities into account to focus on the most important areas and to maximise improvements in ADPKD outcomes.